Family Risk and Protective Factors and Child Development - Yoon, Susan H. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint is devoted to understanding the unique and combined effects of family risk and protective factors on child development across multiple dimensions of functioning (e.g., physical, mental, emotional, behavioral, social, and cognitive).